Estimating the cost of producing grid-connected solar PV in Indonesia - Firdaus A.; Amrina U. (BIO Web of Conferences)
Indonesia has set itself a very challenging set of objectives about introducing renewables into the energy mix, particularly large-scale, on-grid, solar photovoltaic (PV). Being on the equator, Indonesia is blessed with year-round sunlight. Although solar PV is the fastest-growing renewable generation source worldwide, Indonesia has hardly started to install it. One of the reasons for the slow development of solar PV in Indonesia is the lack of information for investors regarding the cost required to build and operate a solar PV over a specified cost recovery period. Therefore, this study aims to estimate the cost of producing grid-connected solar PV in Indonesia. As the results of this study, we have constructed a simple tool that calculates the cash flow of a typical project, and then computes levelised cost of electricity (LCoE), internal rate of return (IRR), payback period (PBP), and return on investment (RoI) to explore the business case faced by investors of solar PV in Indonesia.